2021
DOI: 10.1038/s41467-021-21019-4
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric columnar assemblies from the bowl-to-bowl inversion of aromatic cores

Abstract: Organic ferroelectrics, in which the constituent molecules retain remanent polarization, represent an important topic in condensed-matter science, and their attractive properties, which include lightness, flexibility, and non-toxicity, are of potential use in state-of-the-art ferroelectric devices. However, the mechanisms for the generation of ferroelectricity in such organic compounds remain limited to a few representative concepts, which has hitherto severely hampered progress in this area. Here, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 34 publications
0
64
0
1
Order By: Relevance
“… Reagents and conditions: (a) 439 Br 2 , Fe, nitrobenzene, 80 °C, 2 days; (b) RSNa, dry 1,3-dimethyl-2-imidazolidinone, rt, 8 h; (c) 440 BBr 3 , DCM, 0 °C to rt, then H 2 O; (d) R′Br, K 2 CO 3 , DMF, 75 °C. …”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“… Reagents and conditions: (a) 439 Br 2 , Fe, nitrobenzene, 80 °C, 2 days; (b) RSNa, dry 1,3-dimethyl-2-imidazolidinone, rt, 8 h; (c) 440 BBr 3 , DCM, 0 °C to rt, then H 2 O; (d) R′Br, K 2 CO 3 , DMF, 75 °C. …”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
“…In a recent report, Furukawa, Akutagawa, and Saito et al demonstrated a new method for generation of ferroelectricity based on bowl-to-bowl inversion of trithiasumanene. 440 The attendant dipole inversion was envisioned to induce ferroelectric response in the solid state because of the relatively low inversion barrier compared to corannulene and sumanene. Hexaalkoxytrithiasumanenes 237.4a – d were prepared by applying a dealkylation–realkylation procedure to the ethoxy-substituted precursor 237.3 .…”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
“…However, its activation energy in the solid state is too high because of the formation of tightly-packed 1D-columns; consequently, the application of the bowl-flipping motion of sumanene was first realized in a sulfur analogue, 1,4,7-trithiasumanene, which possesses much a shallower bowl than 2. [16] In this context, we focused on the in-plane motion of 2 in its columnar form, in which convex-concave-type curve-to-curve contacts exist, and we attempted to use this motion to bring out some physical functions. It had already been revealed that the dominant intermolecular interaction present in the crystal packing of sumanene are inter-and intracolumnar weak CH-π interactions between benzylic sp 2 carbons and the π-bowl, rather than intracolumnar π-π interactions (the distance between the two centroids of the bottom six-membered rings in a stacking column of 2 is 3.87 Å).…”
Section: Introductionmentioning
confidence: 99%
“…However, its activation energy in the solid state is too high because of the tightly-packed 1D-column formation and therefore application of the bowl flipping motion of sumanene is first realized in its sulfur analog which possesses much shallower bowl than 2. [16] In this context, we instead focused on the in-plane motion of 2 in its columnar structure, in which "convex-concave" type curveto-curve contacts exist, and attempted to utilize this motion to bring out some physical functions. It is already revealed that the dominant intermolecular interaction formed in the crystal packing of sumanene is both inter-and intra-columnar weak CH-π interactions between the benzylic sp 2 carbon and π-bowl rather than intra-columnar π-π interaction (cf.…”
Section: Introductionmentioning
confidence: 99%